Into that darkness : an examination of conscience - Sereny, Gitta, 1921-2012. (New York : Vintage Books, 1983)
Based on 70 hours of interviews with Franz Stangl, commandant of Sobibor and Treblinka (the largest of the five Nazi extermination camps), this book bares the soul of a man who continually found ways to rationalize his role in Hitler's final solution.
Originally published: London : Deutsch, 1974.
Includes index.
Bibliography: p. 369-372.
The Roger Griffin ComFas Collection
Keywords: Stangl, Franz, -- 1908-1971.; World War, 1939-1945 -- Prisoners and prisons, German; Concentration camps -- Europe